Strengthening the Readiness of Tourism Village Institution Through the Assistance in Developing Standard Operating Procedure: Case Study of Mundu, Klaten Regency - Perwithosuci, Winny; Hidayah, Nur; Praswati, Aflit Nuryulia; Setiawati, Diana; Andriyani, Nur; Fauzan, Ahmad; Wardani, Lusyka Widya (Journal of Community Services and Engagement: Voice of Community (VOC), 2025)
Mundu Village is a village in Indonesia located in Tulung District, Klaten Regency, Central Java Province. The Statistics Indonesia (BPS) revealed that more than 60% of the residents of Mundu Village own cattle. This condition has led the community to utilize cattle manure as a source of renewable energy. Additionally, cattle manure is processed into fertilizer to nourish various plants, some of which serve as a food source for the livestock. This activity is known as zero-waste agriculture. This condition encouraged the Mundu Village government to establish a Tourism Village that offers educational tourism based on renewable energy. Mundu Village already has several buildings to support the realization of the Tourism Village. However, Mundu Village is not yet ready in terms of institutions. The community service team from the Faculty of Economics and Business and the Faculty of Law of Muhammadiyah University of Surakarta provided education and assistance in preparing Standard Operating Procedures (SOPs) to support the acceleration of institutional readiness in the effort to establish an Educational Tourism Village based on Renewable Energy. The activity proceeded successfully, marked by the preparation of a draft SOP that is ready to be approved, supporting the institutional strengthening of the Tourism Village.